Construction of Evaluation Indicator System and Analysis for Low-Carbon Economy Development in Chengdu City of China - Yan Jia; Yuanyuan Huang; Junyang Zhou; Jushuang Sun (Systems)
In order to promote the green and low-carbon transformation of the economy and society, as the economic center of the western region of China, Chengdu actively promotes the national green and low-carbon policies. Some specific measures are proposed to develop Chengdu’s low-carbon economy, such as increasing the ownership of new energy vehicles, promoting the development of park cities and increasing the proportion of clean energy and non-fossil energy, etc. So, in order to accurately evaluate Chengdu’s low-carbon economy-development achievements, firstly, this paper uses literature research to construct an evaluation indicator system for the low-carbon economy development of Chengdu city from five dimensions: economy, energy, technology, environment, and transportation. Then, an improved Analytic Hierarchy Process (AHP) method based on judgment matrices is proposed to determine subjective weights of indicators, while Entropy Weight Method (EWM) and Variation Coefficient (VC) method are used to determine objective weights of the evaluation indicators. Finally, the Technique for Order Preference by Similarity to an Ideal Solution (TOPSIS) is used for the multi-indicator comprehensive evaluation of Chengdu’s low-carbon economy development. The evaluation results show that the comprehensive performance of Chengdu’s low-carbon economy has continued to improve from 2018 to 2023, simultaneously, the main influencing factors and weak links are analyzed, and targeted suggestions and strategies for improvement are put forward to promote the low-carbon economy development of Chengdu city.